Solve the System

(write answer as an ordered pair)

y = 6x - 11

7 - 3y = 2x

(write answer as an ordered pair)

y = 6x - 11

7 - 3y = 2x

(2, 1)

Solve the System

(write answer as an ordered pair)

y = -3x + 5

5x - 4y = -3

(write answer as an ordered pair)

y = -3x + 5

5x - 4y = -3

(1, 2)

Solve the System

(write answer as an ordered pair)

-3x - 3y = 3

y = -5x -17

(write answer as an ordered pair)

-3x - 3y = 3

y = -5x -17

(-4, 3)

Solve the System

(write answer as an ordered pair)

y = -2

3y = 4x - 18

(write answer as an ordered pair)

y = -2

3y = 4x - 18

(3, -2)

Solve the System

(write answer as an ordered pair)

y = 6 + 4x

-5x - y = 21

(write answer as an ordered pair)

y = 6 + 4x

-5x - y = 21

(-3, -6)

Solve the System

(write answer as an ordered pair)

y = 5x - 7

-3x - 2y = -12

(write answer as an ordered pair)

y = 5x - 7

-3x - 2y = -12

(2, 3)

Solve the System

(write answer as an ordered pair)

x = 1 - 3y

x + y = 5

(write answer as an ordered pair)

x = 1 - 3y

x + y = 5

(7, -2)

Solve the System

(write answer as an ordered pair)

x + y = 4

x = 3 - y

(write answer as an ordered pair)

x + y = 4

x = 3 - y

No Solution

Solve the System

(write answer as an ordered pair)

x + y = -6

y = -13 - 5x

(write answer as an ordered pair)

x + y = -6

y = -13 - 5x

(-3, 2)